Assessing the impact of health information orientation and health information literacy on patients’ engagement with health information - Hashmi, Ferhana Saeed; Soroya, Saira Hanif; Mahmood, Khalid (Journal of information science, 2024)
Health information engagement can help individuals to find and use reliable sources of health information to make informed decisions about their health. This helps to improve their health outcomes and prevent unnecessary healthcare costs. Drawing upon the cognitive behavioural theory, this pilot study postulated a model to understand that the consequences of information orientation in terms of information engagement (behaviour), information literacy (cognition) and information avoidance (behaviour) in post-COVID era under health context. Furthermore, the moderation effects of health information literacy (HIL) are also calculated in managing health information avoidance beahvior. This pilot study is conducted in the context of social media exposure to health information by diabetic patients in Pakistani community. The proposed model was tested using Partial Lease Square Structural Equational Modelling (PLS-SEM). The data were collected from 166 diabetic patients (active social media users) through a survey. The study findings suggest that health information orientation on social media leads to HIL and engagement. Whereas, it has significant negative impact towards health information avoidance behaviour. Furthermore, HIL significantly increases health information engagement of diabetic patients. Also, HIL moderates the relationship between health information orientation and information engagement positively, whereas between health information orientation and health information avoidance negatively.